Composite Properties and Micromechanical Analysis of Highly Ductile Cement Composite Incorporating Limestone Powder - Jung Hwan Hyun; Bang Yeon Lee; Yun Yong Kim (Applied Sciences, 2018)
This paper presents the results of an experimental study on the effect of limestone powder on the compressive strength, tensile behavior, and micromechanical parameters of a highly ductile cement composite incorporating limestone powder. Four mixtures were determined according to the replacement ratio of cement with limestone powder. A series of experiments including compressive strength, uniaxial tension, single fiber pullout, and matrix toughness tests were performed. Test results showed that the strength (compressive, initial cracking, and tensile strength) decreased, and that the tensile strain capacity increased, with an increase of the replacement ratio of cement with limestone powder. Micromechanical tests and analysis supported the uniaxial tension test result.